Hubungan Tingkat Pengetahuan Perawat Tentang Kemoterapi Dengan Tindakan Pemberian Kemoterapi Pasien Kanker Payudara - Sri - Hidayati; Gamya Tri Utami; Agrina - - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the relationship of the level of knowledge with actions of nurses in the administration of chemotherapy in breast cancer patients. The method of the study was descriptive correlation with cross – sectional design. The study was conducted at the Arifin Achmad Hospital of the 51 samples by purposive sampling method. Measuring instruments was questionnaires and observation sheets that have been tested for validity and reliability. The analysis of this study were univariate and bivariate analysis by Chi-square test. The results showed that there was a relationship between the level of nurse’s knowledge about chemotherapy with nurse’s actions in giving chemotherapy for patiens with breast cancer in Arifin Achmad Hospital by the p value = 0.041, significant p value ≤ α (0.05). Based on the results, Nurses are expected the nurse to wear self protection  properly, take seminars, trainings or workshops on chemotherapy to improve health care service. Key words : breast cancer, chemotherapy, knowledge and action.